2013
DOI: 10.1590/1516-4446-2012-1051
|View full text |Cite
|
Sign up to set email alerts
|

Religious beliefs and alcohol control policies: a Brazilian nationwide study

Abstract: Objective: The connection between lower alcohol use and religiousness has been extensively examined. Nevertheless, few studies have assessed how religion and religiousness influence public policies. The present study seeks to understand the influence of religious beliefs on attitudes toward alcohol use. Methods: A door-to-door, nationwide, multistage population-based survey was carried out. Selfreported religiousness, religious attendance, and attitudes toward use of alcohol policies (such as approval of publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
25
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 32 publications
1
25
1
5
Order By: Relevance
“…These religious affiliations usually have stronger opinions regarding public policy than do other religious traditions, including advocating for more restrictive alcohol policies. 2 There are distinct differences in alcohol use between religious traditions, as we reported in a recent article. 3 For instance, Afro-Brazilian religions (i.e., Umbanda) utilize alcohol in their rituals, whereas some Brazilian Protestant Evangelicals forbid its use entirely, whether for religious or non-religious purposes.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…These religious affiliations usually have stronger opinions regarding public policy than do other religious traditions, including advocating for more restrictive alcohol policies. 2 There are distinct differences in alcohol use between religious traditions, as we reported in a recent article. 3 For instance, Afro-Brazilian religions (i.e., Umbanda) utilize alcohol in their rituals, whereas some Brazilian Protestant Evangelicals forbid its use entirely, whether for religious or non-religious purposes.…”
mentioning
confidence: 59%
“…2 We agree that cultural values, personality, and stressful life events can have an important influence on alcohol use. In our study, the population was predominantly composed by Catholics (67.3%), followed by Evangelical Protestants (23.3%).…”
mentioning
confidence: 85%
“…One of the interesting findings of Luchetti et al 3 was that religiosity was associated with more restrictive alcohol policies. This, of course, is also true of politically conservative individuals and, despite the association between religiosity and a variety of positive health outcomes, there is strong evidence linking it with politically conservative and prejudiced attitudes, such as homophobia, authoritarianism, and racism.…”
mentioning
confidence: 94%
“…3,4 The vast majority of studies report a negative association between religiosity and alcohol use but, until recently, no data were available for the Brazilian context. Fortunately, this has now been changed with a nationwide study by Lucchetti et al 3 which, like U.S. based research before it, showed that individuals with higher levels of religiosity support more restrictive alcohol polices and report less alcohol abuse. 3 With these results at hand, there is now a need to move further and ask: what are the psychological mechanisms that mediate this relationship?…”
mentioning
confidence: 99%
See 1 more Smart Citation